2021
DOI: 10.1161/circheartfailure.120.008110
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Women Developing Heart Failure After Early Stage Breast Cancer Chemotherapy: A Population-Based Matched Cohort Study

Abstract: Background: The prognosis of heart failure (HF) after early stage breast cancer (EBC) treatment with anthracyclines or trastuzumab is not well-characterized. Methods: Using administrative databases, women diagnosed with HF after receiving anthracyclines or trastuzumab for EBC in Ontario during 2007 to 2017 (the EBC-HF cohort) were categorized by cardiotoxic exposure (anthracycline alone, trastuzumab alone, sequential therapy with both agents) and matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The NSABP-31 CRS predicted the probability of "definite or probable cardiac death or congestive heart failure (CHF) manifested by dyspnea with normal activity or at rest and associated with an absolute decrease in LVEF of greater than 10 percentage points from baseline to a value less than 55% or a decrease of more than 5% to a value below the lower limit of normal". The majority of the cardiac outcomes in this study (95%) occurred within the first 2 years [18].…”
Section: Risk Modelsmentioning
confidence: 80%
See 1 more Smart Citation
“…The NSABP-31 CRS predicted the probability of "definite or probable cardiac death or congestive heart failure (CHF) manifested by dyspnea with normal activity or at rest and associated with an absolute decrease in LVEF of greater than 10 percentage points from baseline to a value less than 55% or a decrease of more than 5% to a value below the lower limit of normal". The majority of the cardiac outcomes in this study (95%) occurred within the first 2 years [18].…”
Section: Risk Modelsmentioning
confidence: 80%
“…To potentially promote more clinical uptake of these models, we sought to assess and compare the performance of these models in a large cohort of women with HER2+ breast cancer treated in a routine clinical practice. We focused on the diagnosis of CTRCD by the end of treatment, as this can affect ongoing cancer treatment and majority of CTRCD events in women with HER2+ early-stage breast cancer occur by the end of the treatment [4,11,18,24]. In our cohort, the NSABP-31 CRS and the HFA-ICOS proformas appear to identify patients with graded risk for CTRCD with the highest risk categories having a 1.7-to-2.4-fold higher risk of CTRCD compared to the lowest risk category.…”
Section: Existing Risk Prediction Modelsmentioning
confidence: 99%
“…34 A more recent 2021 study showed that women with breast cancer developing heart failure (HF) after trastuzumab-based chemotherapy had a lower risk of HF hospital presentations than patients with HF and no cancer. 35 This result was likely driven by the fact that the cohort of patients with breast cancer had fewer co-morbidities despite a diagnosis of malignancy. Moreover, in our study, in patients with breast cancer and SC, a historical diagnosis of breast cancer was far more prevalent than a diagnosis of active cancer (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…A large study of NIS patients in 2018 showed that the diagnosis of breast cancer in patients undergoing PCI was not significantly associated with either in‐hospital mortality or any of the complications studied 34 . A more recent 2021 study showed that women with breast cancer developing heart failure (HF) after trastuzumab‐based chemotherapy had a lower risk of HF hospital presentations than patients with HF and no cancer 35 . This result was likely driven by the fact that the cohort of patients with breast cancer had fewer co‐morbidities despite a diagnosis of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients was small, and it may be the reason for the lack of statistically significant differences in mortality between cancer and noncancer populations. There are also observations in which trastuzumab-treated women who developed heart failure had better prognoses than matched heart failure controls-patients with no cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%